2023
DOI: 10.1021/acs.chemmater.3c02018
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Instability of Titanicone Grown by Molecular Layer Deposition Using TiCl4 and Ethylene Glycol

Hyeongjin Kim,
Jieun Hyun,
Gaeun Kim
et al.

Abstract: Titanicone, obtained through molecular layer deposition (MLD) using TiCl 4 and ethylene glycol (EG), is often regarded as a thin film of titanium ethylene glycolate [Ti(OCH 2 CH 2 O) 2 ]. Nevertheless, titanicone exhibits a distinct vulnerability to moisture, while single crystals of Ti(OCH 2 CH 2 O) 2 remain stable, even in the presence of water. To elucidate the origin of instability, we investigated the pathway of chemical degradation for titanicone using in situ and ex situ analytical methods such as Fouri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
0
0
0
Order By: Relevance
“…Molecular layer deposition (MLD) is an analogue of ALD where molecular fragments are included in the resulting films and may be a route to porous and/or low- k materials. , In prior studies, chemical changes in MLD metalcone films were observed with UV, thermal, and/or ambient exposure, indicating the removal of organics and changes in physical properties. Previously, aluminum oxide-based materials were developed for low- k etch stop applications motivating us to explore the applicability of hafnium-based MLD films for the low- k applications and to better understand the synthesis–structure–composition–property relationships in these materials. ,, In this work, we deposit hafnicone, which is a hybrid hafnium alkoxide film, using MLD and report the thermally induced removal of the organic components and the ability to create low density and low k films relative to HfO 2 . We examine the evolution of chemical, structural, and electrical properties of the as-deposited and annealed hafnicone films in comparison to those of ALD hafnia films.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular layer deposition (MLD) is an analogue of ALD where molecular fragments are included in the resulting films and may be a route to porous and/or low- k materials. , In prior studies, chemical changes in MLD metalcone films were observed with UV, thermal, and/or ambient exposure, indicating the removal of organics and changes in physical properties. Previously, aluminum oxide-based materials were developed for low- k etch stop applications motivating us to explore the applicability of hafnium-based MLD films for the low- k applications and to better understand the synthesis–structure–composition–property relationships in these materials. ,, In this work, we deposit hafnicone, which is a hybrid hafnium alkoxide film, using MLD and report the thermally induced removal of the organic components and the ability to create low density and low k films relative to HfO 2 . We examine the evolution of chemical, structural, and electrical properties of the as-deposited and annealed hafnicone films in comparison to those of ALD hafnia films.…”
Section: Introductionmentioning
confidence: 99%
“… 31 , 32 In prior studies, chemical changes in MLD metalcone films were observed with UV, thermal, and/or ambient exposure, indicating the removal of organics and changes in physical properties. 33 38 Previously, aluminum oxide-based materials were developed for low- k etch stop applications motivating us to explore the applicability of hafnium-based MLD films for the low- k applications and to better understand the synthesis–structure–composition–property relationships in these materials. 32 , 39 , 40 In this work, we deposit hafnicone, which is a hybrid hafnium alkoxide film, 41 using MLD and report the thermally induced removal of the organic components and the ability to create low density and low k films relative to HfO 2 .…”
Section: Introductionmentioning
confidence: 99%